The role of allogeneic stem cell transplantation in Hodgkin’s lymphoma - Sureda, Anna; Domenech, E.; Schmitz, N.; Dreger, Peter (Current treatment options in oncology, 2014)
The treatment of patients with classical Hodgkin’s lymphoma relapsing after autologous stem cell transplantation represents a clear unmet need. Overall long-term outcome is not the same in these patients and therapeutic options in this setting are very heterogeneous and include salvage CT and/or RT followed or not by a second stem cell transplantation, palliative care, new drugs, or biological agents. Despite the absence of prospective, randomized, clinical trials, allogeneic stem cell transplantation either from a HLA identical sibling or a matched, unrelated donor represents an attractive option for those young patients with chemosensitive disease after being treated with a salvage protocol. The use of reduced intensity conditioning regimens has been able to drastically decrease nonrelapse mortality, although relapse rate remains a significant issue in this setting. More intense conditioning protocols could eventually decrease the relapse rate after the allogeneic procedure and, as indicated by a recent retrospective analysis of the Lymphoma Working Party of the European Group for Blood and Marrow Transplantation, nonrelapse mortality does not represent a major problem nowadays for patients with multiply relapsed Hodgkin’s lymphoma. Brentuximab vedotin is an antibody-drug conjugate that selectively delivers monomethyl auristatin E, an antimicrotubule agent, into CD30-expressing cells. Its use has been approved recently for patients with Hodgkin’s lymphoma relapsing after autologous stem cell transplantation. As a single dose, brentuximab vedotin is able to achieve an objective response rate of 75 % with 34 % of the patients achieving a complete remission. Its widespread use will most certainly change the treatment paradigm of this subgroup of patients, either avoiding the allogeneic procedure in some patients or by increasing the group of potential candidates to an allogeneic transplant being used as a “bridge to allo.” Additional information on long-term outcome of patients being treated with this drug or the development of prospective clinical trials in this setting will most probably give some light to this question we have nowadays.
Gesehen am 17.08.2020